Pelatihan Pembuatan Laporan Arus Kas Guna Meningkatkan Good Governance UMKM - Putri Nurmala; Akhmad Sigit Adiwibowo (Abdimisi, 2020)
The Indonesian Institute of Accountants (IAI) (1994: 2) states that financial statements consist of balance sheets, income statements, changes in financial position reports (in the form of cash flow reports), notes and other reports as well as explanatory material that is an integral part of financial statements. Starting in 1994, IAI, through Statement of Financial Accounting Standards (PSAK) number 2 (para. 04), determined that the statement of changes in financial position should no longer be presented as a statement of cash flows, but must be a cash flow statement. As the reason for this change, it is stated that historical cash flow information is useful for: (1) showing the amount, timing and certainty of future cash flows, and (2) examining the accuracy of the estimation of future cash flows. IAI itself issued a special financial accounting standard for MSMEs called Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The method of implementation is carried out by first conducting surveys related to what is needed by MSME players. It turns out that what MSME players need is in line with our PKM theme, namely making cash flow reports. After that, for five weeks, twice a week, our team helps create cash flow reports for MSME players using the Microsoft Excel application. The result of this PKM is the realization of cash flow reports for MSME players in the Microsoft Excel application. In addition, MSME actors now also understand the importance of making relevant and accountable cash flow reports in order to improve their business good governance.